Food Insecurity in U.S. Households That Include Children With Disabilities. (October 2016) - Sonik, Rajan; Parish, Susan L.; Ghosh, Subharati; Igdalsky, Leah
The authors examined food insecurity in households including children with disabilities, analyzing data from the 2004 and 2008 panels of the Survey of Income and Program Participation, which included 24, 729 households with children, 3, 948 of which had children with disabilities. Logistic regression models were used to estimate the likelihood of food insecurity after adjusting for adult disability status, income, and other sociodemographic factors. Compared to other households with children, those including children with disabilities were more likely to report household food insecurity of any kind, very low household food security, and child food insecurity. Families raising children with disabilities were also more likely to receive Supplemental Nutrition Assistance Program benefits. These results suggest that children with disabilities face an increased risk of experiencing food insecurity and that there is a pressing need to improve the safety net system for these children.